Analisis Sektor Industri Pengolahan Terhadap Produk Domestik Regional Bruto di Kabupaten Tolitoli Periode 2016-2020 Andi Herman Jaya - Jaya, Andi Herman (Universitas Syiah Kuala, 2023)
This study aims to determine the magnitude of the contribution of the Manufacturing Industry Sector to Gross Regional Domestic Product in Tolitoli Regency for the 2016-2020 period. The form of this research is descriptive quantitative. The data used in this study used secondary data from the Central Bureau of Statistics of Tolitoli Regency. By using a contribution analysis tool to calculate the contribution percentage in each year in Tolitoli Regency. The results show that the contribution of the processing industry sector for the period 2016 to 2019 has decreased continuously, but in 2020 the contribution of the processing industry sector in Tolitoli Regency has begun to increase by 0.06 percent and with very low criteria.